Rarely seen bilateral posterior shoulder fracture dislocation: simultaneous bilateral hemiarthroplasty - Fatih Dogar; Duran Topak; Okkes Bilal; Nuh Dundar (Journal of the Pakistan Medical Association, 2022)
Posterior shoulder dislocation is a rare condition, while bilateral posterior shoulder fracture is extremely rare. Dislocations with a fracture of the bilateral posterior shoulder are observed more often after epileptic seizures. As dislocations with posterior shoulder fracture are rare, clinicians sometimes experience difficulty in diagnosing it timely. Although it can be diagnosed and treated early, based on a proper shoulder examination and accurate radiological imagery. In the treatment of posterior shoulder dislocations, closed reduction can be performed at an early stage, while methods of osteosynthesis with open reduction or arthroplasty are the most frequently used procedures at delayed stage. In this study, it was shown for the first time in literature, that a very rare case of dislocation with bilateral posterior shoulder fracture after epileptic seizure, in a 68 years old patient, had good clinical and functional results, following simultaneous hemiarthroplasty treatment. Keywords: Shoulder, Posterior fracture dislocation, Bilateral, Hemiarthroplasty, Seizure.